2006
DOI: 10.1038/nature04559
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling in primates reveals a rapid evolution of human transcription factors

Abstract: Although it has been hypothesized for thirty years that many human adaptations are likely to be due to changes in gene regulation 1 , almost nothing is known about the modes of natural selection acting on regulation in primates. Here we identify a set of genes for which expression is evolving under natural selection. We use a new multi-species complementary DNA array to compare steady-state messenger RNA levels in liver tissues within and between humans, chimpanzees, orangutans and rhesus macaques. Using estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
253
4
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(285 citation statements)
references
References 29 publications
21
253
4
1
Order By: Relevance
“…Phylogenetically distant comparisons had a smaller sample size than close comparisons and so were biased toward large estimates of expression divergence (7). Another study of primate-expression divergence using species-specific probes found that, in the majority of cases, a constant level gene expression across the phylogeny could not be rejected (24). Although this result is consistent with stabilizing selection, a low rate of neutral divergence will have the same effect.…”
Section: Discussionmentioning
confidence: 41%
“…Phylogenetically distant comparisons had a smaller sample size than close comparisons and so were biased toward large estimates of expression divergence (7). Another study of primate-expression divergence using species-specific probes found that, in the majority of cases, a constant level gene expression across the phylogeny could not be rejected (24). Although this result is consistent with stabilizing selection, a low rate of neutral divergence will have the same effect.…”
Section: Discussionmentioning
confidence: 41%
“…It is generally accepted that genetic changes in both cis-and trans-regulatory elements contribute remarkably more than changes in functional genes to phenotypic variation (Doebley and Lukens, 1998;Carroll, 2000;Gilad et al, 2006). Among the regulatory elements that account for herbivore resistance in plants, those involved in early responses are particularly interesting because many play key roles in transducing responses to various environmental stresses into changes in downstream gene expression and eventually into changes in phenotypic traits.…”
mentioning
confidence: 99%
“…4,10,23 Briefly, large number of quantitative changes in gene expression is found among primates in the initial study, 2 but follow-up studies had somewhat conflicting results. Some studies support a neutral model of expression divergence, 11,12,14,25 while other studies 5,9,17 showed the general existence of stabilizing constraints. Some studies have also found positive selection in primate or mammal expression divergence.…”
Section: Introductionmentioning
confidence: 96%
“…Some studies have also found positive selection in primate or mammal expression divergence. 5,13 There are also many studies on expression divergence in non-mammal species, 3,16,[18][19][20]24 most support a stabilizing selection model but do not exclude the existence of neutral or positive factors.…”
Section: Introductionmentioning
confidence: 99%